Strategi Peningkatan Kinerja Rumah Tahanan Negara Kelas IIB Kefamenanu Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Nusa Tenggara Timur Dalam Mendapatkan Predikat Wilayah Bebas Korupsi Dan Wilayah Birokrasi Bersih Dan Melayani - Klau, Ferdinandus; Kase, Petrus; Daulay, Pardamean (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The Corruption-Free Region (WBK) and the Clean and Serving Bureaucratic Area (WBBM) are predicates from the government given to work units that are completely free from practices of corruption, collusion and nepotism, as well as to clean and healthy work units honest in serving the community. The purpose of this study was to describe and analyze what were the inhibiting factors of the Class IIB Kefamenanu Rutan as a UPT that had not yet received the WBK/WBBM predicate and to describe and analyze the strategy in obtaining the WBK/WBBM predicate in the Class IIB Kefamenanu Rutan using the SOAR approach. This type of research uses descriptive qualitative research methods, where this method can produce research in the form of ten inhibiting factors for Class IIB Rutan not getting the title as WBK/WBBM, namely supporting facilities and infrastructure, job analysis and workload analysis, internalization of WBK and WBBM on employees, employee comfort zones, WBK/WBBM budgets, notification of reasons for failure, the impact of the COVID-19 pandemic, solidity and cohesiveness of the employee work team, apathetic work culture, and leadership changes in the current year. There are four recommended strategies, namely the need to increase internal rotation and mutation, measurable rewards and punishments, the formation of an imitation study team, and the need to involve subordinates in every collaboration between organizations.